The Impact of Ukrainian War Refugees on Rental Prices in Europe: A Panel Data Analysis - Adam Czerniak (Critical Housing Analysis)
This study examines the impact of Ukrainian war refugees on actual rental prices in 27 European countries. Using panel data regression analysis for the period 2017Q1-2023Q1, the study found that inflation, house price growth, and interest rates were the primary drivers of rental price growth after February 2022. The study also showed that an inflow of Ukrainian refugees equal to 1% of the host country’s population translated into an increase in rental price growth of 0.2-0.3%, but this effect was not statistically significant at the 5% probability threshold. Auxiliary estimations revealed the statistical significance of Ukrainian migration when adjusting for the stringency of rent controls and size of the rental market.